2005
DOI: 10.1186/1471-2458-5-68
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of varicella and herpes zoster in Massachusetts as measured by the Behavioral Risk Factor Surveillance System (BRFSS) during a period of increasing varicella vaccine coverage, 1998–2003

Abstract: Background: The authors sought to monitor the impact of widespread varicella vaccination on the epidemiology of varicella and herpes zoster. While varicella incidence would be expected to decrease, mathematical models predict an initial increase in herpes zoster incidence if re-exposure to varicella protects against reactivation of the varicella zoster virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
107
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(120 citation statements)
references
References 37 publications
6
107
1
6
Order By: Relevance
“…In contrast, two further US studies report increases in zoster incidence rates following varicella vaccination. A telephone survey in Massachusetts found an increase in zoster incidence from 2.77 to 5.25 cases per 1000 people between 1999 and 2003 [33]. A study using the Veterans Administration database reported that between 2000 and 2007 (when vaccine coverage was higher), zoster increased from 3.10 to 5.22 episodes per 1000 people aged ≥40 years, although rates per year were not standardized for age [34].…”
Section: Temporal Changes In Incidencementioning
confidence: 99%
“…In contrast, two further US studies report increases in zoster incidence rates following varicella vaccination. A telephone survey in Massachusetts found an increase in zoster incidence from 2.77 to 5.25 cases per 1000 people between 1999 and 2003 [33]. A study using the Veterans Administration database reported that between 2000 and 2007 (when vaccine coverage was higher), zoster increased from 3.10 to 5.22 episodes per 1000 people aged ≥40 years, although rates per year were not standardized for age [34].…”
Section: Temporal Changes In Incidencementioning
confidence: 99%
“…The reason for this trend is currently unknown. [4][5][6] According to a hypothesis proposed by Hope-Simpson, exposure to primary varicella or subclinical latent varicella zoster virus can boost varicella zoster virus-specific immunity and reduce the risk of HZ. 7 A liveattenuated vaccine for varicella was introduced into the US vaccination schedule in 1995 for children aged 12 months or older, with subsequent significant declines in the incidence of varicella.…”
mentioning
confidence: 99%
“…3 However, studies examining the effect on the overall population rates in the United States with observation periods ranging from 1992 through 2010 have been inconclusive. [3][4][5][6]9 A live-attenuated vaccine for HZ has been available in the United States since 2006. The vaccine reduces the likelihood of developing HZ by 51.3% in individuals aged 60 years or older, and vaccinated individuals who develop HZ usually have less severe disease.…”
mentioning
confidence: 99%
“…Ähnliche Beobachtungen liegen aus den USA vor [4,6,32]. In multivariaten Analysen ließ sich in den USA bislang kein Zusammenhang zwischen dem Anstieg der Zoster-Inzidenz und der Varizellenimpfung nachweisen [6], zumal der Herpes zoster durch zahlreiche Faktoren wie Alter, Geschlecht, Komorbidität und Weiteres deutlich beeinflusst wird.…”
Section: Diskussionunclassified